Awareness of the Regulatory Framework Supporting E-Commerce: An Empirical Analysis - Satinder Kumar; Shallu Sehgal (Proceeding of International Conference on Science, Health, And Technology, 2022)
The world is changing at a remarkable pace and so does the world of marketing. The limited options to communicate with the target audience have been widening. Even technology has profoundly changed the way consumers process communication. In the last few years, the internet has played a significant role in many fields of the economy as it is commonly defined as a global media. The internet has been largely used in commerce and management. Electronic commerce, typically written as e-commerce or E-Commerce, is the trading or facilitation of trading in products or services using computer networks, such as the Internet. The rapid adoption of the Internet as a commercial medium has caused firms to experiment with innovative ways of commerce thus changing the pattern of commerce strategies. The primary motive of the study was to investigate the awareness level of respondents regarding the regulatory framework of E-Commerce. The present study was exploratory research by means of primary data analysis wherein an attempt was made to identify the awareness level of respondents regarding the regulatory framework of e-commerce with the help of a self-structured questionnaire. The questionnaire was based on the five-point Likert scale ranging from not at all aware to completely aware and convenience sampling was used to collect the data from respondents (250) residence of Punjab and Union Territory of Chandigarh. Further, the chi-square technique was used to test the null hypothesis as to whether there was a significant relationship between regulatory framework, gender and monthly income attributes. It was observed that female respondents were more aware as compared to male respondents regarding the regulatory framework of e-commerce. On the basis of monthly income attribute, 15000-30000 income group’s respondents were not aware of the regulatory framework of e-commerce but in the next income group ranging from 50000-75000 were aware of the regulatory framework of the e-commerce. Keywords: Regulatory framework, Awareness level, E-Commerce, Spamming, Privacy, Spyware etc.